Hansole client management system - Chananuka, Lincoln G. (Midlands State University, 2017)
The “main objective of developing a Client management system was triggered by the need to improve and manage client more effectively. The current system shows several bottlenecks which include Hansole Investments failing to remind all its clients to make payments whenever these payments are due to be paid since they keep records about payments manually. There is no effective contact between the client and the company. A feasibility study was carried out to determine if the system cloud be developed and the results shows that it was viable to develop. The system was developed us C# programing language Asp.net since it is a web based application Parallel changeover strategy was used to implement the system so that the old system and the new system can work together until the new system is fully stable and users fully appreciate how it works. Maintenance of the system will be conducted as an on-going process to correct all errors that may arise while the system is in use. The system can be further developed in the future by incorporating integrating it with other system that are available such as bulk SMS bulk mailer and domain main” account..